Biocatalysis of carboxylic acid reductases: phylogenesis, catalytic mechanism and potential applications. Issue 4 (30th January 2018) - Qu, Ge; Guo, Jinggong; Yang, Dameng; Sun, Zhoutong
Abstract : Recent advances in carboxylic acid reductases and their practical applications in bio-cascade processes. Abstract : In recent decades, biocatalysis has attracted more and more attention, contributing significantly to synthetic organic chemistry and biotechnology and thereby advancing the development of greener and more sustainable synthetic processes. As a versatile enzyme, carboxylic acid reductases (CARs) are widely distributed in bacteria, fungi and plants. Recent seminal studies focusing on CARs have demonstrated that they can efficiently and selectively reduce a broad range of carboxylic acid substrates to their corresponding aldehyde moieties, which constitutes a very difficult transformation using chemical methods. However, the full potential of CARs is yet to be explored. In this review, we summarize the progress of CARs from an evolutionary point of view, including the convergence/divergence between CARs and knowledge of the catalytic mechanism. Particular emphasis is placed on recent advances in practical applications as well as future developments.